Antitumor immunostimulatory effect via cell-killing action of a novel extracorporeal blood circulating photodynamic therapy system using 5-aminolevulinic acid - Hidetaka Maegawa; Masayuki Kohashi; Yasuo Harada; Akira Tanaka; Shimpei Kajiwara; Takashi Fujimoto; Hidehiro Atagi; Kenta Kaneda (Scientific Reports)
Abstract This study investigated whether intravenous administration of tumor cells killed by photodynamic therapy (PDT) with 5-aminolevulinic acid (5-ALA) had antitumor effects on distal tumors. Furthermore, a novel extracorporeal blood circulating 5-ALA/PDT system was developed. 5-ALA/PDT- (low or high irradiation) or anticancer drug–treated cells were intravenously administered to rats in a glioma cancer model. CD8+ T cell infiltration into the tumor and expression of calreticulin were examined. The cell-killing effect in the circulating PDT system and protoporphyrin IX (PpIX) accumulation were evaluated. An antitumor effect was observed only with preadministration of low-irradiated 5-ALA/PDT-treated cells and was characterized by the infiltration of CD8+ T cells into the tumor. In low-irradiated cells, several types of cell death were observed, and cell surface calreticulin expression increased over time. A method for the intravenous administration of 5-ALA/PDT-treated cells along with extracorporeal blood circulation was then developed to target hematologic malignancies. Gradually cell death in the circulating PDT system and tumor-specific PpIX accumulation was confirmed using hematopoietic tumor cells. Thus, the extracorporeal blood circulating 5-ALA/PDT system has a direct cell-killing effect and an antitumor effect via induced immune activity and illustrates a new therapeutic strategy for hematologic malignancies.